Risperidone inhibits voltage-gated sodium channels - Brauner, Jan M.; Heßler, Sabine; Groemer, Teja W.; Alzheimer, Christian; Huth, Tobias (European Journal of Pharmacology, 2014)
In contrast to several other antipsychotic drugs, the effects of the atypical antipsychotic risperidone on voltage-gated sodium channels have not been characterized yet, despite its wide clinical use. Here we performed whole-cell voltage-clamp recordings to analyze the effects of risperidone on voltage-dependent sodium currents of N1E-115 mouse neuroblastoma cells carried by either endogenous sodium channels or transfected NaV1.6 channels. Risperidone inhibited both endogenous and NaV1.6-mediated sodium currents at concentrations that are expected around active synaptic release sites owing to its strong accumulation in synaptic vesicles. When determined for pharmacologically isolated NaV1.6, risperidone inhibited peak inward currents with an IC50 of 49 µM. Channel block occurred in a state-dependent fashion with risperidone displaying a fourfold higher affinity for the inactivated state than for the resting state. As a consequence of the low state dependence, risperidone produced only a small, but significant leftward shift of the steady-state inactivation curve and it required concentrations >= 30 µM to significantly slow the time course of recovery from inactivation. Risperidone (10 µM) gave rise to a pronounced use-dependent block when sodium currents were elicited by trains of brief voltage pulses at higher frequencies. Our data suggest that, compared to other antipsychotic drugs as well as to local anesthetics and sodium channel-targeting anticonvulsants, risperidone displays an unusual blocking profile where a rather low degree of state dependence is associated with a prominent use-dependent block.
EVALuna2:2444